Kolokasi Dalam Narasi Tentang Liburan Siswa kelas V di SDN Layungsari 2 Kota Bogor - Rahmatillah, Fikhi; Helmanto, Fachri; Effane, Anne (LPPM Institut Pendidikan Nusantara Global, 2025)
Lexical collocation becomes a major focus. Elementary school children face challenges in choosing the right words to describe their holiday experiences clearly and interestingly. In facing this problem, it is important for teachers to guide students in expanding their vocabulary, choosing words that are appropriate to the holiday context, and combining lexical collocations in creative ways to build interesting and memorable stories. This study aims to determine the lexical collocation of words in narratives about fifth-grade students' holidays. This type of research is a corpus linguistics method with a qualitative approach. The data used in this study are written data, namely narrative essays about fifth-grade students' holidays. The data collected were 22 students. Researchers analyzed the results of students' writings using the AntConc application. The results of this study show that the most frequent lexical collocation patterns in fifth-grade students' holiday narratives at SDN Layungsari 2 are the collation patterns of adjectives + verbs, verbs + nouns, adverbs + adjectives, and verbs + adverbs. Holiday writing is an expression of happiness from students and locations that indicate nouns. These results indicate that the lexical collocation patterns used by students reflect their tendency to express happiness, describe activities, and mention locations clearly, thus supporting the function of holiday narratives as a medium for expressing personal experiences and emotions.